2022
DOI: 10.1615/jenvironpatholtoxicoloncol.2021039648
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rk2 Protects against Ulcerative Colitis via Inactivating ERK/MEK Pathway by SIRT1

Abstract: Background: Chinese traditional medicine is widely used in the treatment of ulcerative colitis (UC). Ginsenoside Rk2 is a newly discovered dammarane triterpenoid saponin isolated from ginseng. Our study aimed to investigate the effects of Ginsenoside Rk2 on UC.Methods: Human clones of colorectal adenocarcinoma Caco-2 cells and human intestinal epithelial THP-1 cells were co-cultured to establish a UC model in vitro. Cell viability and apoptosis were analyzed by cell counting kit 8 (CCK-8) and flow cytometry as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In addition, the abnormal immune response-mediated inflammatory response is a key factor in promoting the carcinogenesis of ulcerative colitis (UC) to CRC, and slowing down the inflammatory process prevents the carcinogenesis of UC ( Yang et al, 2013 ; Li et al, 2021 ). Ginsenoside Rk2 reduce the secretion of pro-inflammatory cytokines, such as Interleukin-1 β (IL-1β), Interleukin-6 (IL-6), Interleukin-10 (IL-10), TNF-α, in the vitro UC model established by co-culturing Caco-2 cell clones with THP-1 cells in a concentration-dependent manner, and slow down the inflammatory process by inhibiting the activation of the extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MEK) pathway ( Huang et al, 2022 ).…”
Section: Ginsenosides Regulate Immune Response In the Colorectal Tumo...mentioning
confidence: 99%
“…In addition, the abnormal immune response-mediated inflammatory response is a key factor in promoting the carcinogenesis of ulcerative colitis (UC) to CRC, and slowing down the inflammatory process prevents the carcinogenesis of UC ( Yang et al, 2013 ; Li et al, 2021 ). Ginsenoside Rk2 reduce the secretion of pro-inflammatory cytokines, such as Interleukin-1 β (IL-1β), Interleukin-6 (IL-6), Interleukin-10 (IL-10), TNF-α, in the vitro UC model established by co-culturing Caco-2 cell clones with THP-1 cells in a concentration-dependent manner, and slow down the inflammatory process by inhibiting the activation of the extracellular signal-regulated kinase (ERK)/mitogen-activated protein kinase (MEK) pathway ( Huang et al, 2022 ).…”
Section: Ginsenosides Regulate Immune Response In the Colorectal Tumo...mentioning
confidence: 99%
“…Ginsenosides are representative glycosides for the treatment of IBD [ 129 ]. Ginsenoside RK2 restored cellular function in human intestinal epithelial THP-1 cells by inactivating the ERK/MEK pathway and reducing the release of inflammatory factors [ 139 ]. Ginsenoside Rg1 can condition intestinal flora by inducing macrophage polarization, which reduces the abundance of Bacteroides and Staphylococcus and increases the levels of flora-associated metabolites [ 130 ].…”
Section: Pharmacological Interventions For Ibd and Their Effects On G...mentioning
confidence: 99%
“…Rk2 is a rare dehydroprotopanaxadiol saponin isolated from steamed ginseng samples [ 33 ]. Only one study reported the bioactivity of Rk2 with protective effects against ulcerative colitis in vitro [ 34 ]. Therefore, this study aims to investigate the probable protective effects of Rk2 against alcoholic liver injury in mice and further elucidate its underlying mechanisms targeting hepatic NLRP3 and intestinal NLRP6 inflammasome signaling pathways.…”
Section: Introductionmentioning
confidence: 99%